IMPROVING STUDENT’S ACHIEVEMENT IN WRITING NEWS ITEM TEXT BY USING VIDEO - Ahmad Rifa’i Ritonga; Tjut Ernidawati (Universitas Negeri Medan, 2014)
This study focuses on improving students’ achievement in writing news item textby using video as a media. This study was conducted by using classroom actionresearch. The subject of this research was the grade X students of MAN 2 ModelMedan. Thirty students were taken as the sample. The research was conducted intwo cycles. The first cycle was conducted in three meetings, and the second cyclewas also conducted in three meetings. The instruments for collecting data werequantitative data (essay test) and qualitative data (observation sheet, diary note,and questionnaire sheet). Based on the data analysis, students’ score keptimproving in every test. The mean of the students’ score in the first competencewas 71.37, the second competence test was 75.74, and the third competence testwas 82.4. The result showed that video improved students’ achievement in writingnews item text.